18F-Fluoroestradiol PET/CT Correctly Diagnosed 18F-FDG–Avid Inflammatory Lymph Nodes in a Patient With Estrogen Receptor–Positive Breast Cancer. (May 2018) - Yamane, Tomohiko; Ueda, Shigeto; Seto, Akira; Kuji, Ichiei
Abstract : Abstract: A 77-year-old woman with left breast cancer received 18 F-FDG PET/CT for initial staging, and 18 F-FDG–avid lymph nodes were observed in the bilateral axillae. As estrogen receptor (ER) status of primary lesion was positive, the patient also received 18 F-fluoroestradiol ( 18 F-FES) PET/CT. Unlike primary lesion, no remarkable 18 F-FES uptakes in the lymph nodes were observed. 18 F-FDG uptakes in the nodes were finally interpreted as inflammation. 18 F-FES PET that can noninvasively evaluate the ER status may have a potential to reveal the pathology of the false-positive lesion observed in 18 F-FDG PET for patients with ER-positive breast cancer.